1991
DOI: 10.1007/bf01606502
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of oesophageal melanocytosis

Abstract: Four examples of an endoscopically detected oesophageal melanotic lesion were examined by light microscopy, light microscope histochemistry and transmission electron microscopy, and were compared with 13 control samples of normal oesophageal epithelium. By light microscopy, pigmented melanocytes lacking atypia and mitoses were observed amongst the keratinocytes in the basal layer of the oesophageal mucosa. Junctional activity was absent. The mechanism of pigmentation was studied and found to consist of: an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1
6

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 20 publications
0
41
1
6
Order By: Relevance
“…2 Compound melanosomes have never been reported in melanosis of the urinary bladder. Indeed, these complexes were welldocumented by Yamazaki et al 13 in melanosis esophagi in man, with which our case shares many ultrastructural findings. We detected the presence of BPV-2, a common agent responsible for severe bladder pathology in cattle, including cancer.…”
mentioning
confidence: 54%
“…2 Compound melanosomes have never been reported in melanosis of the urinary bladder. Indeed, these complexes were welldocumented by Yamazaki et al 13 in melanosis esophagi in man, with which our case shares many ultrastructural findings. We detected the presence of BPV-2, a common agent responsible for severe bladder pathology in cattle, including cancer.…”
mentioning
confidence: 54%
“…Genellikle özofagus orta ve alt 1/3'lük kısmında görülmektedir (1,2). Nadir görülen ancak iyi tanımlanmış bir antitedir.…”
Section: Discussionunclassified
“…However, the proliferation of melanocytes might also arise from the scattered stromal neuroectodermal cells or from pluripotent epithelial stem cells [2] . The proliferation of melanocytes is rarely observed with an estimated incidence of about 0.07%-0.15% in patients undergoing endoscopy [3] . Results of a recent study [2] and our case, however, indicate that melanocytes are much more frequently seen in association with reactive changes in the squamous epithelium, such as chronic esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon was first described in 1963 by De la Pava, who found melanocytes in 4% of his autopsy material from the esophagus [1] . Subsequent studies showed that the incidence of esophageal melanocytes ranges 2.5%-8% [2,3] . The increased number of esophageal melanocytes along the epithelio-stromal junction is considered benign and has been described in association with chronic esophagitis, squamous epithelial hyperplasia and infiltrating squamous carcinoma of the esophageal mucosa [2] .…”
Section: Introductionmentioning
confidence: 99%